2019
DOI: 10.1016/j.aanat.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

The morphological variations of the lateral pterygoid muscle: A systematic review

Abstract: Background: The lateral pterygoid muscle (LPM) has been described in many anatomical and functional studies. The morphology of the LPM is still under debate because of its deep location in the infratemporal fossa and the difficulties to approach this area with different anatomical methods. Although it has been generally accepted that this muscle is mainly composed of two separate parts, other forms have been described in the past. Objectives: To conduct a systematic literature review regarding the anatomy and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Nevertheless, the number of lateral pterygoid muscle heads remains controversial. It is commonly a two-headed muscle, but one-headed or three-headed muscles have also been reported [ 46 , 49 , 50 ]. Detailed findings of the origins and insertions of an anatomical study suggest that the lateral pterygoid muscle is a single muscle with no clear border, containing fibers in various directions, indicating that a two-head muscle pattern would be indicated by the differences in the convergences of the muscle fibers [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the number of lateral pterygoid muscle heads remains controversial. It is commonly a two-headed muscle, but one-headed or three-headed muscles have also been reported [ 46 , 49 , 50 ]. Detailed findings of the origins and insertions of an anatomical study suggest that the lateral pterygoid muscle is a single muscle with no clear border, containing fibers in various directions, indicating that a two-head muscle pattern would be indicated by the differences in the convergences of the muscle fibers [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Detailed findings of the origins and insertions of an anatomical study suggest that the lateral pterygoid muscle is a single muscle with no clear border, containing fibers in various directions, indicating that a two-head muscle pattern would be indicated by the differences in the convergences of the muscle fibers [ 49 ]. In contrast, a recent systematic review reported that the frequency of one-headed lateral pterygoid muscles ranged from 7.7% to 26.7%, two-headed muscles from 61.4% to 91.1%, and three-headed muscles from 4.0% to 35.0% [ 50 ]. The difference in efficacy of BoNT therapy between jaw closing and jaw opening dystonia may be associated with the anatomical variability of the lateral pterygoid muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The lateral pterygoid muscle crosses the upper part of the ITF from anteromedial to posterolateral [ 19 , 22 ]. In most of the cases (61.4–91.1%), it is formed by two heads, one arising from the infratemporal surface of the greater wing of the sphenoidal bone and from the infratemporal crest (superior head) and one from the lateral surface of the lateral pterygoid plate (inferior head) [ 22 , 23 ]. Possible variations of lateral pterygoid muscle with single or triple heads have been reported respectively between 7.7 and 26.7%, and 4.0 and 35.0% of cases [ 23 ].…”
Section: Anatomy Of Infratemporal Fossamentioning
confidence: 99%
“…In most of the cases (61.4–91.1%), it is formed by two heads, one arising from the infratemporal surface of the greater wing of the sphenoidal bone and from the infratemporal crest (superior head) and one from the lateral surface of the lateral pterygoid plate (inferior head) [ 22 , 23 ]. Possible variations of lateral pterygoid muscle with single or triple heads have been reported respectively between 7.7 and 26.7%, and 4.0 and 35.0% of cases [ 23 ]. These heads converge in a postero-lateral direction to insert into the pterygoid fovea (a convex space on the neck of the mandible), the articular disc, and the capsule of the temporomandibular joint [ 22 , 23 , 24 ].…”
Section: Anatomy Of Infratemporal Fossamentioning
confidence: 99%
See 1 more Smart Citation